Evaluation of three-dose fosfomycin tromethamine in the treatment of patients with urinary tract infections: an uncontrolled, open-label, multicentre study - Shan Chen; Yong Yang; Bo Yang; Ming Chen; Kai Zhang; Yi Wang; Lu-Dong Qiao; Bo Zheng; Hong-Feng Guo; Yuan-Jie Niu; Ben-Kang Shi; Wei-Min Yang; et al. (BMJ Open)
Objective To evaluate the clinical and microbiological efficacy and safety of three doses of 3 g fosfomycin tromethamine administered orally to treat lower urinary tract infections.Design and participants This prospective, uncontrolled, open-label study was conducted in 12 medical centres in China, between January and December 2011. According to the diagnosis criteria of Chinese Guidelines on Urological Infections, patients (18–70 years) with acute uncomplicated cystitis, recurrent lower urinary tract infection or complicated lower urinary tract infection received three doses of 3 g fosfomycin tromethamine orally, at days 1, 3 and 5.Primary and secondary outcome measures Efficacy endpoints (clinical efficacy, microbiological efficacy and overall efficacy) were evaluated on day 15. Clinical symptoms, physical signs, urinalysis, liver and kidney function, patient records and evaluation of adverse events (AEs) and serious AEs up to day 15 were evaluated for analysis of safety.Results 361 patients were included in the full analysis set, 356 in the safety analysis set and 335 in the per-protocol set (PPS). In the PPS, the clinical efficacy rates at day 15 for acute uncomplicated cystitis, recurrent lower urinary tract infection and complicated lower urinary tract infection were 94.71% (179/189), 77.22% (61/79) and 62.69% (42/67), respectively. The microbiological efficacy rates (day 15) were 97.65% (83/85), 94.44% (34/36) and 83.87% (26/31), respectively. The overall efficacy rates (day 15) were 95.29% (81/85), 77.78% (28/36) and 64.52% (20/31), respectively. 20/356 (5.6%) patients reported drug-related AEs, the most common being diarrhoea. No serious drug-related AEs were reported.Conclusions This fosfomycin tromethamine dosing regimen showed clinical and microbiological efficacy with some AEs and good tolerability in patients with acute uncomplicated cystitis, recurrent lower urinary tract infection and complicated lower urinary tract infection.